Inducible HIV-1 Reservoir Quantification: Clinical Relevance, Applications and Advancements of TILDA - Lungu, Cynthia (Front Microbiol, 2021)
The presence of a stable HIV-1 reservoir persisting over time despite effective antiretroviral suppression therapy precludes a cure for HIV-1. Characterizing and quantifying this residual reservoir is considered an essential prerequisite to develop and validate curative strategies. However, a sensitive, reproducible, cost-effective, and easily executable test is still needed. The quantitative viral outgrowth assay is considered the gold standard approach to quantify the reservoir in HIV-1-infected patients on suppressive ART, but it has several limitations. An alternative method to quantify the viral reservoir following the reactivation of latent HIV-1 provirus detects multiply-spliced tat/rev RNA (msRNA) molecules by real-time PCR [tat/rev induced limiting dilution assay (TILDA)]. This article provides a perspective overview of the clinical relevance, various applications, recent advancements of TILDA, and how the assay has contributed to our understanding of the HIV-1 reservoir.